Members of the GH3 Family of Proteins Conjugate 2, 4-D and Dicamba with Aspartate and Glutamate. (8th August 2018) - Chiu, Li-Wei; Heckert, Matthew J; You, You; Albanese, Nicholas; Fenwick, Tamara; Siehl, Daniel L; Castle, Linda A; Tao, Yumin
Abstract: Auxin homeostasis is a highly regulated process that must be maintained to allow auxin to exert critical growth and developmental controls. Auxin conjugase and hydrolase family proteins play important roles in auxin homeostasis through means of storage, activation, inactivation, response inhibition and degradation of auxins in plants. We systematically evaluated 60 GRETCHEN HAGEN3 (GH3) proteins from diverse plant species for amino acid conjugation activity with the known substrates jasmonic acid (JA), IAA and 4-hydroxybenzoate (4-HBA). While our results largely confirm that Group II conjugases prefer IAA, we observed no clear substrate preference among Group III proteins, and only three of 11 Group I proteins showed the expected preference for JA, indicating that sequence similarity does not always predict substrate specificity. Such a sequence–substrate relationship held true when sequence similarity at the acyl acid-binding site was used for grouping. Several GH3 proteins could catalyze formation of the potentially degradation-destined aspartate (Asp) and glutamate (Glu) conjugates of IAA and the synthetic auxins 2, 4-D and dicamba. We found that 2, 4-D–Asp/Glu conjugates, but not dicamba and IAA conjugates, were hydrolyzed in Arabidopsis and soybean by AtILL5- and AtIAR3-like amidohydrolases, releasing free 2, 4-D in plant cells when conjugates were exogenously applied to seedlings. Dicamba–Asp or dicamba–Glu conjugates were not hydrolyzed in vivo in infiltrated plants nor in vitro with recombinant amidohydrolases. These findings could open the door for exploration of a dicamba herbicide tolerance strategy through conjugation.